Caracterização estrutural e dielétrica da matriz BaBi4Ti4O15(BBT) com adição de Bi2O3 - Almeida, Patricia Matos Viana de (2015)
The composed ceramics for ferroelectrics oxides of the family of the Aurivillius possess properties prominently, as natural anisotropy, optic properties electro and piezoelétricas properties that are necessary for devices of electronic the technological area of sensors, integrated semiconductors, circuits, oscillators, capacitors, batteries, transducers for high temperature, etc. The BaBi4Ti4O15 (BBT) belongs the family of the Aurivillius and these are structures, which contain perovskitas in its separate interior for flourite layers. The perovskitas are a small oxide classroom that will count ions e with great load, which chains form one octahedro of on oxygen for the extremities forming continue of oxygen-metal-oxygen and this arrangement is that it favors the ferroelectricity. The structural, electric and ferroelectrics properties of the BaBi4Ti4O15 are analyzed by means of addition of ions in its pure such as Pb2+, Al3+, Ga3+, In3+, You5+, among others similar structure to improve such properties. This work considers to investigate the BaBi4Ti4O15 with Bismuth oxide addition (Bi2O3), inquiring its structural and dielectric properties through techniques of diffraction of Ray, spectroscopy Raman, spectroscopy of impedance, and still to search improvement of the synthesis how much to the time for formation of phase and homogenization of particles of the material. The results of structural characterization through the diffraction de Ray and of the Rietveld refinement of the ceramic samples of BaBi4Ti4O15 with different molar concentrations (1, 2, 5 and 10%) of Bi2O3 in had confirmed the formation of an only phase and the presence to them of all the components of BaBi4Ti4O15, not finding impurities (inside of the limitations techniques of the program). The structural characterization through the spectroscopy raman in showed to characteristic peaks (274,7 cm-1 and 552,75 cm-1) of a structure with octahedro, characterizing a perovskite structure to them. In the picnometria, the analysis of the density, showed that the presence of Bi2O3 depending on its percentage can increase or diminish the density of the sample of BaBi4Ti4O15, being that the compacting biggest was in the amount of 10% of fondant, around 6g/cm3. Already through the spectroscopy of dielectric impedance the gotten data if had shown coherent with the results found in literature. A transition of ferroelectric phase between 420ºC and 450ºC was found, verified in the graphs of the mechanism of the dielectric module, the energy of activation and the dielectric Constant; also if it verified that the BBT has a dielectric behavior that does not follow the model of Debye, moreover, had been observed loads of transports of long and short reach in a mechanism of conduction activated thermally and still was found a contribution of an ionic conduction in the material.